Perceived Importance and Practices of Programme Development Steps and Principles by Extension Supervisors in the Department of Agriculture, Malaysia - Wan Ismail, Wan Hanisah (1993)
Enormous efforts have been made by the government to improve local extension services. However, weaknesses and discrepancies in extension services relating to programme development are still being voiced out. This study was an attempt to determine the importance and frequency of practice in the field, of the steps and principles of programme development in the field as perceived by extension supervisors in the Department of Agriculture. Another objective of the study was to identify the constraints faced by the extension supervisors, who are graduates of the Universiti Pertanian Malaysia, in their effort to carry out the programming steps and principles as being taught in the university. The respondents were Agriculture Officers and 50 Assistant Agriculture Officers from three state Departments of Agriculture in Peninsular Malaysia. Questionnaire schedules were used for data collection. Follow-up group interviews were also conducted with selected respondents. The analysis of data revealed that all except two of the eight programming steps (analysis of the situation and preparation of the programme document) taught in the University were perceived as important in programme development. However, none of those steps were reported to be frequently practised in the field. Similarly, five of the principles of programme development tested (except Cooperation and coordination) were perceived as important, but none had been consistently emphasised by the extension supervisors during the process of extension programme development. The extension supervisors faced constraints with three of the eight programming steps. The biggest constraints were with evaluation and accountability. The most frequently mentioned constraints were, problems related to clients who were part-time farmers; lack of time due to work over-load on the part of the extension supervisors; lack of adequate knowledge and skills in extension programme development; lack of up-to-date information about the clients; insufficient funds; low cooperation among extension officers; environmental situations; political influence and low interagency cooperation. Several recommendations were suggested to improve the programme development practices in the DOA. These include strengthening the pre-service and in-service training by the DOA and UPM, reviewing the teaching approach by these two institutions, training local leaders in programme development, making early provisions for cooperation and coordination with other agencies, and providing clear statements of roles of those involved in programme development. It was also recommended that the extension supervisors be relieved from most administrative duties so as to enable them to give more concentration on extension activities. Lastly, a follow-up study using the qualitative approach was proposed to determine an indepth picture of the status of programme development practices and constraints faced which resulted in their low level of practice in the field.